Should oral contraceptives be available without prescription? - Trussell, J (1993)
In this paper, it is argued that oral contraceptives should be available without prescription. Prescription status entails heavy costs, including the dollar, time, and psychological costs of visiting a physician to obtain a prescription, the financial and human costs of unintended pregnancies that result from the obstacle to access caused by medicalization of oral contraceptives, and administrative costs to the health care system. After a review and evaluation of the reasons for strict medical control of oral contraceptives in the United States, safety concerns anticipated in response to the proposal discussed here are addressed. Also, concerns that prescription status is necessary for efficacious use are evaluated. It is concluded that neither safety nor efficacy considerations justify prescription status for oral contraceptives. Revised package design and patient labeling could allow women to screen themselves for contraindications, to educate themselves about danger signs, and to use oral contraceptives safely and successfully. Several alternatives to providing oral contraceptives by prescription with current package design and labeling and selling them over the counter are suggested; the proposals discussed would make these safe and effective contraceptives easier to obtain and to use.